Pengaruh Program Magang Dan Studi Independen Bersertifikat (MSIB) Merdeka Belajar Kampus Merdeka (MBKM) Terhadap Peningkatan Keterampilan Dan Kesiapan Kerja Mahasiswa Universitas Hamzanwadi - Rizkiwati, Baiq Yuliana; Rapii, Muhammad; Juniarta, Isnayanti Firdaus; Yati, Yati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to determine the effect of the Internship and Certified Independent Study (MSIB) Freedom of Learning Independent Campus (MBKM) Program on Improving Skills and Work Readiness of Hamzanwadi University Students partially with a quantitative correlation research type using primary data sources collected using distributed questionnaires. This population is Hamzanwadi University students who have participated in the Internship and Certified Independent Study (MSIB) Freedom of Learning Independent Campus (MBKM) batch 1 to 5, as many as 40 samples using random sampling techniques with the slovin formula. Data processing with descriptive statistical analysis techniques, prerequisite tests, simple linear regression tests, and T hypothesis tests. Based on the results of data processing, there is a partial positive influence between the variables of the Certified Internship and Independent Study Program (MSIB) Freedom of Learning Independent Campus (MBKM) on Improving the Skills of Hamzanwadi University Students with a significance value of 0.019 <0.05, the variables of the Certified Internship and Independent Study Program (MSIB) Freedom of Learning Independent Campus (MBKM) on the Work Readiness of Hamzanwadi University Students with a significance value of 0.014 <0.05. In the determination coefficient test on the Y1 variable, the results were 13.6% and Y2 obtained results of 14.7%, meaning that the improvement of skills and work readiness can be clarified by the Independent Internship and Independent Study Program (MSIB) Freedom of Learning Independent Campus (MBKM) variable with the remaining 86.4% and 85.3% which are clarified by the influence of other variables that are not observed and explained in this research